2013
DOI: 10.1186/1471-2393-13-243
|View full text |Cite
|
Sign up to set email alerts
|

Provider perspectives on constraints in providing maternal, neonatal and child health services in the Lao People’s democratic republic: a qualitative study

Abstract: BackgroundTo reduce its high maternal and neonatal mortality rate and meet Millennium Development Goals four and five, Lao PDR has adopted a national ‘Strategy and Planning Framework of Implementation of Maternal, Neonatal and Child Health Services’. This paper reports on implementation constraints identified in three demonstration sites.MethodsThe objectives of this paper are to analyse health worker perceptions of the implementation of the strategy and constraints faced during implementation. A qualitative d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 21 publications
7
28
0
Order By: Relevance
“…Also, equipment donated by development partners enabled health facilities to offer free services. However, buildings are dilapidated, health facilities lack public utilities and functional ambulances to support referrals, equipment is stacked and not tailored to the scope of services provided by facilities, which are consistent with findings of several studies [18,24,36]. Equally, the study found that donation of seed stock for the drug revolving fund and subsequent procurement through the central medical stores improved availability of quality-assured drugs in health facilities.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Also, equipment donated by development partners enabled health facilities to offer free services. However, buildings are dilapidated, health facilities lack public utilities and functional ambulances to support referrals, equipment is stacked and not tailored to the scope of services provided by facilities, which are consistent with findings of several studies [18,24,36]. Equally, the study found that donation of seed stock for the drug revolving fund and subsequent procurement through the central medical stores improved availability of quality-assured drugs in health facilities.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, shortage of appropriate qualified health workers, worse in remote areas, constrained provision of maternal, neonatal and child health services in the Lao People’s Democratic Republic and three African countries, where health workers had preference for urban posts [19,36]. Though presence of SURE-P staff improved the availability of health workers, postings and transfers of health workers to less busy or urban health facilities limit responsiveness of health facilities and contribute to declining quality of care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Chodzaza & Bultemeier 2010;Sychareun et al 2013). In our study, the SBA training, the supply of drugs, and support from community members and health managers were nominated as strengths of the enabling environment by all SBAs.…”
Section: Discussionmentioning
confidence: 99%
“…This study reanalyzed the data used by Ngan and colleagues [16] and Sychareun and colleagues [17]. The former study focused on the utilization of maternal health care services, and the latter examined constraints experienced by service providers when providing maternal and child health services.…”
Section: Methodsmentioning
confidence: 99%